Burnout Among Student-Athlete Services Professionals - Rubin, Lisa M.; Moreno-Pardo, Maria D. (My University, 2018)
Literature on job burnout in athletics is limited to coaches, trainers, athletes, and administrators. Among student-services professionals, studies have focused on those in student support services, student affairs and mid-level administration. The purpose of this study was to explore factors why student-athlete services professionals burn out and consider leaving the profession. Themes from the literature on burnout include work overload, work environment/autonomy, evaluation/supervision, social support, and values/motivation/expectations. Burnout also serves as the theoretical framework for this study based on these six themes. The researchers sought volunteers from the N4A membership willing to be interviewed about burnout in the student-athletes services profession. We conducted interviews in Fall 2016 with 38 professionals in the field including directors, assistant/associate directors, advisors, learning specialists, and student-athlete development professionals with varying levels of experience in the field, which inform athletic administrators of the factors which lead to burnout and high turnover. The goal is to share this information as a mode of preventing burnout among talented student-athletes services professionals and their leaving the profession.
Keywords: Burnout; Athletic Advising; Student-Athlete Services; Higher Education; College Athletics